ISOLATION AND IDENTIFICATION OF LACTOSE-FERMENTING YEAST CELLS FROM DAIRY PRODUCTS - Myrzakhmetova , G.M.; Ualieva , P.S.; Abdieva , G.Zh. (Eurasian Journal of Applied Biotechnology, 2023)
One of the most valuable substrates in terms of the composition of important nutritional and biological factors is dairy products. The direct use of dairy products for food purposes is characterized by a combination of high acidity and special organoleptic characteristics. Yeast cells play the role of active ingredients in them, as they have a pronounced lacto- and bifidogenic effect. Lactose-fermenting yeasts are considered one of the main objects of molecular genetics and are widely used as producers of a number of biologically active substances. In recent years, a fundamentally new direction of industrial processing of milk whey and chubat has been actively and purposefully formed, as well as the basis for obtaining derivative components, which are targeted products. The purpose of the research work: isolation and identification of lactose-fermenting yeasts from milk whey and chubat. Growth dynamics of yeast strains were studied in Sabouro's nutrient medium, under aerobic growth conditions, and were also carried out using the methods of Bradford and Glushanov. In the course of the study, the microbiological indicators and taxonomic composition of the microbial community of milk whey of "Amiran" LLP and chubat of "Sarzhailau" LLP were studied. Physico-chemical and organoleptic characteristics of dairy products were studied. 2 yeast strains were isolated from substrate samples. The morphological and cultural properties of the isolated yeasts were studied, and as a result, IL1 and IL2 strains were identified as IL1-Pichia fermentans, IL2-Pichia fermentans.